Implementation of Sustainable Development Concept in Hotel A Surabaya - Nuke Puspawardani; Kresno Eka Mukti; Angsar Nur Himawan; Happy Ratna Sentosa (Institute of Advanced Engineering and Science, 2015)
Hospitality is one of the important sectors in the growth of the Indonesian Economy, which it continues to increase each year. But on the other hand it also has a negative impact. The higher use of the hotel, the higher the resource and energy expended to serve the guests of the hotel. This study aims to determine the implementation of sustainable development concept of Hotel A in Surabaya. This hotel is under auspices of the Accor Group, one of international hotel management groups, which already implemented the concept of sustainable development. To achieve the objectives of the study, the researcher using qualitative analysis techniques to process the primary and secondary data obtained, to find the answer on how far the application of sustainable development at the Hotel A. The research results show that Hotel A has conducted various measures to support sustainable development in several aspects. But they just apply 3 of 7 pillars of ecology as envisioned by the Accor Group. This study shows the aspects of eco-friendly management that can be carried out by a hotel.